2018
DOI: 10.1038/s41467-018-04946-7
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state vibrational dynamics toward the polaron in methylammonium lead iodide perovskite

Abstract: Hybrid organic–inorganic perovskites have attractive optoelectronic properties including exceptional solar cell performance. The improved properties of perovskites have been attributed to polaronic effects involving stabilization of localized charge character by structural deformations and polarizations. Here we examine the Pb–I structural dynamics leading to polaron formation in methylammonium lead iodide perovskite by transient absorption, time-domain Raman spectroscopy, and density functional theory. Methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(200 citation statements)
references
References 66 publications
(59 reference statements)
8
179
0
1
Order By: Relevance
“…33 Moreover, recent work shows that the polaron formation can be also related to inorganic lattice vibration/deformation. 29,79,80 For example, the energy of the I-Pb-I bending mode is 21cm −1 , therefore we can expect that it is active even at low temperatures. The transition from a static disorder at very low temperature to a dynamic disorder at higher temperatures is accompanied by a significant drop of the PL emission intensity (see blue points in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…33 Moreover, recent work shows that the polaron formation can be also related to inorganic lattice vibration/deformation. 29,79,80 For example, the energy of the I-Pb-I bending mode is 21cm −1 , therefore we can expect that it is active even at low temperatures. The transition from a static disorder at very low temperature to a dynamic disorder at higher temperatures is accompanied by a significant drop of the PL emission intensity (see blue points in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several computational works investigated the atomistic details of polarons in LHPs, both in 3D as well as in 2D and 0D perovskites. By using a DFT cluster approach Neukirch et al demonstrated that localization of electrons and hole polarons is promoted by the orientation of organic cations and manifest through a stretching, compression of the octahedra PbI bonds, respectively .…”
Section: Large Polarons—static Vision: Lattice Rearrangement Phononsmentioning
confidence: 99%
“…Previously, we have also observed that due to the degeneracy at the bottom of the conduction band in the absence of SOC, the estimated Jahn-Teller distortions and displacements are larger than those observed in experiment. 68 In spite of these limitations, general trends across the materials series are predicted correctly.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…44 The JT distortions in HP materials is important in small polaron formation of electrons and is discussed in this manuscript and other previous manuscripts. 68,69 The JT distortion is intimately linked to electronic degrees of freedom and is important signature of small polaron formation. 69,70 Consequently, it manifests in removing an electronic degeneracy, opening a band gap and favoring a particular electronic state.…”
Section: Accepted Manuscriptmentioning
confidence: 99%